Antiviral Treatment among Pregnant Women with Chronic Hepatitis B - Lin Fan; Kwame Owusu-Edusei; Sarah F. Schillie; Trudy V. Murphy (Hindawi Limited, 2014)
Objective. To describe the antiviral treatment patterns for chronic hepatitis B (CHB) among pregnant and nonpregnant women. Methods. Using 2011 MarketScan claims, we calculated the rates of antiviral treatment among women (aged 10-50 years) with CHB. We described the pattern of antiviral treatment during pregnancy and ≥1 month after delivery. Results. We identified 6274 women with CHB during 2011. Among these, 64 of 507 (12.6%) pregnant women and 1151 of 5767 (20.0%) nonpregnant women received antiviral treatment (P < 0.01). Pregnant women were most commonly prescribed tenofovir (73.4%) and lamivudine (21.9%); nonpregnant women were most commonly prescribed tenofovir (50.2%) and entecavir (41.3%) (P < 0.01). Among 48 treated pregnant women with an identifiable delivery date, 16 (33.3%) were prescribed an antiviral before pregnancy and continued treatment for at least one month after delivery; 14 (29.2%) started treatment during the third trimester and continued at least one month after delivery. Conclusion. Among this insured population, pregnant women with CHB received an antiviral significantly less often than nonpregnant women. The most common antiviral prescribed for pregnant women was tenofovir. These data provide a baseline for assessing changes in treatment patterns with anticipated increased use of antivirals to prevent breakthrough perinatal hepatitis B virus infection.